Emerging School Readiness Profiles: Motor Skills Matter for Cognitive- and Non-cognitive First Grade School Outcomes - Kamphorst, Erica; Cantell, Marja; Van Der Veer, Gerda; Minnaert, Alexander; Houwen, Suzanne (Frontiers in Psychology, 2021)
A promising approach for studying school readiness involves a person-centered approach, aimed at exploring how functioning in diverse developmental domains conjointly affects children’s school outcomes. Currently, however, a systematic understanding lacks of how motor skills, in conjunction with other school readiness skills, affect a child’s school outcomes. Additionally, little is known about longitudinal associations of school readiness with non-academic (e.g., socioemotional) school outcomes. Therefore, we examined the school readiness skills of a sample of Dutch children (N = 91) with a mean age of 3 years and 4 months (46 % girls). We used a multi-informant test battery to assess children’s school readiness in terms of executive functions (EFs), language and emergent literacy, motor skills, and socioemotional behavior. During the spring term of a child’s first grade year, we collected academic and non-academic (i.e. EFs, motor skills, socioemotional- and classroom behavior, and creative thinking) school outcomes. A latent profile analysis revealed four distinct profiles. Children within the ‘Parent Positive’ (29%) profile were rated positively by their parents, and performed variably on motor and language/emergent literacy skills tests. The second profile - ‘Multiple Strengths’ (13%)- consisted of children showing strengths in multiple domains, especially with respect to motor skills. Children from the third profile -‘Average Performers’ (50%)- did not show any distinct strengths or weaknesses, rather displayed school readiness skill levels close to, or just below the sample mean. Finally, the ‘Parental Concern’ (8%) profile was characterized by high levels of parental concerns, while displaying slightly above average performance on specific motor and language skills. Motor skills clearly distinguished between profiles, next to parent-rated EFs and socioemotional behavior, and to a lesser extent emergent literacy skills. School readiness profiles were found to differ in mean scores on first grade academic achievement, parent- and teacher-rated executive functions, motor skills, parent-rated socioemotional functioning, and prerequisite learning skills. The pattern of mean differences was complex, suggesting that profiles could not be ranked from low too high in terms of school outcomes Longitudinal studies are needed to disentangle the interaction between emerging school readiness of the child and the surrounding context.